Enhancing Cultural Awareness through Project-Based Learning: A Study on Historical Preservation in Kazakhstan - Nurdauletova, Bibaisha; Artykbaev, Zhambyl; Amirbekova, Aigul; Koshimova, Bibatpa; Otarova, Akmaral; Zhetkizgenova, Aliya (Journal of ethnic and cultural studies, 2024)
The Mangistau region of Kazakhstan is rich in cultural heritage and is characterized by various toponyms reflecting its multifaceted history. In the context of the Mangistau region, incorporating the cultural and historical context into the program helps students form a deeper connection with the region and its tangible and intangible heritage. By learning historical place names and their etymological origins, students gain insights into the history and cultural development of the region. This study investigates the teaching of etymological analysis of historical toponyms of the Mangistau region through project-based teaching and its impact on student’s attitudes toward history and interest in historical and cultural values. The study employed a quasiexperimental design based on quantitative research methods. According to this design, pre-test results were used to divide the groups into experimental and control groups. The participants comprised 61 students (Experimental group n=31; Control group n=30) studying in the 2nd grade of a high school in Almaty, Kazakhstan, in the 2023-2024 academic year. The experimental group was taught project-based learning activities for six weeks, while the control group was taught historical toponyms and etymological analysis of the Mangistau Region using traditional teaching methods and techniques. The Attitudes Toward Historical and Toponymy Subjects Scale and the Interest in Historical and Cultural Values Scale were used as data collection instruments. The pre-test and post-test results of the experimental and control groups were analyzed using the Independent Samples t-test technique. The analysis revealed that the students in the experimental group demonstrated significantly higher mean scores in the post-test compared to the control group. The findings indicated that teaching with a project-based learning approach on historical toponyms and etymological analysis of the Mangistau region increased students’ interest in and attitudes toward historical and cultural values.